2018
DOI: 10.3171/2018.2.peds17724
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative complications and risk factors in neuromuscular scoliosis surgery

Abstract: OBJECTIVEHigh rates of perioperative complications are associated with deformity correction in neuromuscular scoliosis. The current study aimed to evaluate complications associated with surgical correction of neuromuscular scoliosis and to characterize potential risk factors.METHODSData were retrospectively collected from a single-center cohort of 102 consecutive patients who underwent spinal fusions for n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 20 publications
1
43
0
1
Order By: Relevance
“…Note that the screws are in line with the remainder of the fusion construct with a notable decrease in wound infections, respiratory complications, and implant-related complications. Toll et al [37] reviewed 102 patients and found a rate of complications of 27%. Eighty percent of those were considered major complications.…”
Section: Complicationsmentioning
confidence: 99%
“…Note that the screws are in line with the remainder of the fusion construct with a notable decrease in wound infections, respiratory complications, and implant-related complications. Toll et al [37] reviewed 102 patients and found a rate of complications of 27%. Eighty percent of those were considered major complications.…”
Section: Complicationsmentioning
confidence: 99%
“…Owing to preexisting underlying diseases, as well as difficulties in the operation itself, patients with NMDs have more complications. According to Toll et al, 56 a 27% complication rate was reported among 102 patients, and nonambulatory status, pulmonary comorbidity, and history of seizure were the risk factors for complications. In addition, it was reported that a diagnosis of myelomeningocele and higher intraoperative blood loss were associated with a high risk of complications.…”
Section: Postoperative Complicationsmentioning
confidence: 99%
“…Generally, thoracolumbar deformity surgery in patients with NMDs is more likely to have higher complication rates than that in non-NMD patients. [56][57][58] Rumalla et al 57 reported an overall complication rate of 40.1% in patients undergoing fusion surgery out of 2,154 neuromuscular scoliosis patients between 2002 and 2011. In a review study of the Scoliosis Research Society Morbidity and Mortality database, Reames et al 59 reported that complications occurred in 1,971 cases out of a total of 19,360 cases (10.2%), including 6.3% in patients with idiopathic scoliosis, 10.6% in patients with congenital scoliosis, and 17.9% in patients with neuromuscular scoliosis, which was the highest complication rate.…”
Section: Postoperative Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vornehmlich Ponte-Osteotomien u. SPO, seltener PSO u. VCR 0 -3 % Coe et al [95] Lonner et al [96] Kim et al [97] Koller [98] Finocchiaro [99] Kongenitale Skoliose Dorsale und/oder ventrale Fusion, Epiphyseodesen, VCR, Hemivertebra-Resektion, PSO, Distraktionsverfahren 0 -14 % Reames et al [14] Smith et al [15] Ayvaz et al [16] Kaspiris et al [17] Neuromuskuläre Skoliose Dorsale und dorsoventrale Fusion mit/ohne Pelvis-Einschluss 1,8 -16,7 % Rumalla et al [100] Turturro et al [101] Cognetti et al [102] Toll et al [103] Degenerative rigide Deformitäten (fixierte sagittale Imbalance, degenerative Skoliose)…”
Section: Neurovaskuläre Anatomieunclassified